Effects of heat source/sink on MHD flow and heat transfer over a shrinking sheet with mass suction (Chemical Engineering Research Bulletin, 2011)
An analysis is made to study the effects heat source/sink on the steady two dimensional MHD boundary layer flow and heat transfer past a shrinking sheet with wall mass suction. In the dynamic system, a uniform magnetic field acts normal to the plane of flow. The governing partial differential equations are transformed into self-similar ordinary differential equations using similarity transformations. Then the obtained self-similar equations are solved by finite difference method using quasilinearization technique. From the analysis it is found that the velocity inside the boundary layer enhances with increase of wall suction and magnetic field and accordingly the thickness of the momentum boundary layer decreases. The temperature decreases with Hartmann number, Prandtl number and heat sink parameter and the temperature increases with heat source parameter. Furthermore, for strong heat source heat absorption at the sheet occurs.Key words: MHD boundary layer, heat transfer, shrinking sheet, heat source/sink, suction.DOI: http://dx.doi.org/10.3329/cerb.v15i1.6524 Chemical Engineering Research Bulletin 15 (2011) 12-17